Open Multicentre Study of the P2T Receptor Antagonist AR-C69931MX Assessing Safety, Tolerability and Activity in Patients with Acute Coronary Syndromes - Storey, Robert F.; Oldroyd, Keith G.; Wilcox, Robert G.; the Investigators; on behalf of (Thrombosis and Haemostasis, 2001)
Platelet aggregation is the central process in the pathophysiology of acute coronary syndromes. ADP contributes to thrombosis by activating platelets, and AR-C69931MX is a specific antagonist of this process acting at the P2T receptor. At 5 hospitals, 39 patients with unstable angina or non-Q wave myocardial infarction, who were receiving aspirin and heparin, were administered intravenous AR-C69931MX with stepped dose increments over 3 h to a plateau of either 2 μg/kg/min for 21 h (Part 1; n = 12) or up to 69 h (Part 2; n = 13) or 4 μg/kg/min for up to 69 h (Part 3: n = 14). Safety parameters, platelet aggregation (PA) induced by ADP 3 μmol/L (impedance aggregometry), bleeding time (BT) and plasma concentrations of AR-C69931XX were assessed. AR-C69931MX was well tolerated. 33 patients completed the study. There were no deaths at 30 days and no serious adverse events attributed to AR-C69931MX. Trivial bleeding (56%) was common. At 24 h, mean inhibition of PA was 96.0 ± 8.6, 94.9 ± 14.4 and 98.7 ± 2.1% and BT was 9.5 ± 8.4, 14.0 ± 9.7 and 16.0 ± 11.1 min for Parts 1, 2 and 3 respectively. At 1 h post-infusion, mean inhibition of PA was 36.2 ± 39.2, 20.7 ± 25.9 and 40.7 ± 36.7% respectively. 90% patients had a plasma half-life for AR-C69931XX of 9 min. In conclusion, AR-C69931MX is a potent, short-acting platelet ADP receptor antagonist suitable for further studies as an antithrombotic agent.
Keywords: Platelet aggregation inhibitors; adenosine diphosphate; P2 receptors; unstable angina; heparin